A theoretical comparison between the simplex method and the basic line search algorithm. (2nd January 2016) - Dumaldar, Mahesh N.
Abstract : A theoretical comparison between the simplex method (SM) and the basic line search method (BLSA) is presented. The explicit formulae for the upper and lower bounds in the BLSA are provided using SM. Further, it is shown that both methods are operationally equivalent.